A comparative study of split advection algorithms on the moment-of-fluid (MOF) method for incompressible flow. (15th April 2023) - Ye, Zhouteng
Abstract: The moment-of-fluid method (MOF) is known as an extension of the volume-of-fluid method with piecewise linear interface construction (VOF-PLIC). In this study, several directional splitting advection algorithms are extended from the VOF-PLIC method to the MOF method. These methods, along with some existing directional splitting algorithms, are presented in detail, especially on the geometrical and non-geometrical nature of the advection algorithm. In addition, a simple and efficient analytic form to calculate the volume and centroid of the intersection polyhedron in 3D is proposed. Several numerical tests, including both 2D and 3D tests, are carried out to investigate mass conservation and geometrical error. Numerical results suggest that the mixed EI and LE scheme (EILE2D) (Aulisa et al., 2003) has the overall best performance in 2D, and Weymouth and Yue's scheme (WY) has the overall best performance in 3D. Highlights: A variety of VOF-PLIC advection schemes are extended to MOF advection. A simple and efficient algorithm to calculate the volume and centroid during MOF advection is proposed. Comparative study evaluates the performance of different split advection algorithm in both 2D and 3D.